1961
DOI: 10.1113/jphysiol.1961.sp006818
|View full text |Cite
|
Sign up to set email alerts
|

Anion permeability of the synaptic and non‐synaptic motoneurone membrane

Abstract: It was discovered by Coombs, Eccles & Fatt (1955a) that the hyperpolarization of the inhibitory post-synaptic potential (IPSP) changed to a depolarization when Cl-ions were injected either by diffusion or electrophoretically into cat spinal motoneurones. This effect was satisfactorfly explained by assuming that, when activated, the inhibitory post-synaptic membrane is permeable to C1-ions. A similar effect was obtained for Br-, NO3-and SCN-ions, but not for HC03-, CH3C02-, SO42m HPO and glutamate ions. Since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
78
0

Year Published

1964
1964
1993
1993

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(88 citation statements)
references
References 39 publications
(44 reference statements)
10
78
0
Order By: Relevance
“…In the present experiments the relative anion permeability of the post-synaptic membrane was estimated from the relative value of the conductance change during GABA action and it was observed that the (Robinson & Stokes, 1955). Filled circles: naked ion sizes (Araki et al 1961). …”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In the present experiments the relative anion permeability of the post-synaptic membrane was estimated from the relative value of the conductance change during GABA action and it was observed that the (Robinson & Stokes, 1955). Filled circles: naked ion sizes (Araki et al 1961). …”
Section: Discussionmentioning
confidence: 74%
“…The anion species which pass through the activated post-synaptic membrane have been investigated on mammalian motoneurones (Coombs et al 1955;Araki et al 1961;Ito et al 1962), Mauthner cells (Asada, 1963), and snail ganglion cells (Kerkut & Thomas, 1964). In these experiments various anions were injected into nerve cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…
Ito & Oscarsson, 1961; Coombs, Eccles & Fatt, 1955).3. Studied with potassium chloride filled micropipettes.
…”
mentioning
confidence: 99%